A comprehensive investigation of structural and magnetic phase stability, electronic, magnetic and thermoelectric properties of Co2FeZ (Z = Al, Ga, Si, Ge, S, Se and Te) Full Heusler alloys. (1st November 2022) - Saleem, Muhammad; Shakil, M.
Abstract: A series of full Heusler (FH) alloys Co2 FeZ (Z = Al, Ga, Si, Ge, S, Se and Te) have been investigated using density functional theory (DFT) with full potential-linearized augmented plane wave (FPLAPW) method within generalized gradient approximation (GGA) and Perdew-Burke-Ernzerhof (PBE) functional. Most stable structures are determined by considering four different atomic arrangements i.e. L21 -I/II (conventional) and XA-I/II (inverse) configurations. Stable magnetic phases like anti-ferromagnetic (AFM), nonmagnetic (NM) and ferromagnetic (FM) are evaluated and results revealed that FM phase is the most stable of all alloys. Spin band structures are calculated by applying GGA and GGA + mBJ approach. The results showed the half metallic nature of Co2 FeAl and Co2 FeGe alloys. The obtained band diagrams are compared with density of states (DOS) and revealed that the both Fe and Co atoms contributes maximum in total magnetic moment (MM). The calculated values of total magnetic moment (MT ) of all compounds range from 4 to 6 μB and are in well agreement with the findings of Slater-Pauling Rule (SPR). Both alloys i.e. Co2 FeAl and Co2 FeGe showed 100% level of spin polarization (SP) at Fermi level. Mean field approximation (MFA) is employed to determine Curie temperature (Tc) and the values thus obtained are higher than room temperature. Furthermore, the thermoelectric parameters i.e. Seebeck coefficient (S) along with thermal (κ) and electrical (σ) conductivities for both Co2 FeAl and Co2 FeGe alloys are calculated and discussed in detail. The obtained results envisaged that the investigated alloys are suitable candidates for thermoelectric and spintronic applications. Highlights: Structural stability using conventional and inverse atomic arrangements. Determination of spin band diagrams using GGA and GGA + mBJ. Half metallic behavior through spin polarization. Calculations of Curie temperature and magnetic moment. Study of thermoelectric parameters.